2017
DOI: 10.1177/2325967117697287
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Osseous Malalignment and Realignment Procedures in Knee Ligament Surgery: A Systematic Review of the Clinical Evidence

Abstract: Background:Failure rates of knee ligament surgery may be high, and the impact of osseous alignment on surgical outcome remains controversial. Basic science studies have demonstrated that osseous malalignment can negatively affect ligament strain and that realignment procedures may improve knee joint stability.Hypothesis/Purpose:The purpose of this review was to summarize the clinical evidence concerning the impact of osseous malalignment and realignment procedures in knee ligament surgery. The hypotheses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 64 publications
(114 reference statements)
0
40
0
4
Order By: Relevance
“…In HTO with anterior closure, the intra-operative hyperextension of the knee joint should not exceed 5° [34]. At the moment, it is not absolutely clear what are the essential limits for slope correction [41].…”
Section: Tibial Slopementioning
confidence: 99%
See 1 more Smart Citation
“…In HTO with anterior closure, the intra-operative hyperextension of the knee joint should not exceed 5° [34]. At the moment, it is not absolutely clear what are the essential limits for slope correction [41].…”
Section: Tibial Slopementioning
confidence: 99%
“…It appears that it is unnecessary to correct a first degree varus malposition in order to achieve adequate knee stability and that this does not bring any increased risk of graft failure [33,41]. However, studies have shown that second or third degree varus malposition may be associated with an increase in tension in the anterior cruciate ligament and that this can then lead to graft failure [41,42]. On the other hand, it is also emphasised that even a minor deviation increases the stress in the anterior cruciate ligament and lateral collateral ligament.…”
Section: Corrections In the Frontal Planementioning
confidence: 99%
“…Das betrifft einerseits den Banderhalt durch Refixation oder Augmentation und andererseits die Rekonstruktion der anterolateralen Gelenkecke [1,4,9]. Auch die Bedeutung von Beinachse und Reklination des Tibiaplateaus (posteriorer Slope) für die Stabilisierung des Gelenks findet verstärkt Beachtung [12,13]. Diese Beobachtungen zeigen, dass die operative Therapie der VKB-Ruptur und der anterolateralen Rotationsinstabilität komplex geworden ist.…”
Section: Vorderes Kreuzband -Neue Operationstechnikenunclassified
“…Vários pesquisadores têm estudado a influência do "slope" tibial no risco de ruptura primária e de falha da reconstrução do LCA (BURNHAM et al, 2017a;DEJOUR et al, 2017;MAROUANE et al, 2014a;SMITH et al, 2012;SONNERY-COTTET et al, 2014b;STIJAK;HERZOG;SCHAI, 2008;TISCHER et al, 2017b), porém ainda não há consenso sobre quando e nem como controlar esse possível fator de risco. O objetivo deste trabalho foi produzir dados, para confrontar as informações da literatura e possibilitar um melhor entendimento da aplicabilidade da medição do ângulo proximal da tíbia no cotidiano ortopédico.…”
Section: Lista De Abreviaturas E Siglasunclassified
“…, há recurvato do joelho, situação também conhecida como "flambagem" do joelho (NOYES; BARBER-WESTIN;HEWETT, 2000). Alguns autores, nos casos de lesão do LCA e degeneração do compartimento medial, também acreditam que esse a osteotomia proximal da tíbia seja necessária (TISCHER et al, 2017a)…”
unclassified